Cardiac Surgery Operations on the Heart and Great Vessels in Adults and Children - Ziemer, Gerhard; Haverich, Axel.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2017)
This text describes and illustrates with some 700 detailed anatomic and surgical drawings the whole spectrum of surgical procedures employed to treat acquired and congenital diseases of the heart and great vessels in adults and children. A rather traditional chapter on history of cardiac surgery precedes chapters dedicated to quality improvement, followed by ICU management in adult and pediatric cardiac surgery, and techniques of extracorporeal circulation in both age groups. Further special topics are cardiovascular tissue engineering, minimally invasive cardiac surgery, endovascular treatment of aortic diseases, and cardiac assist devices, including total artificial heart. Written by 71 internationally recognized experts from 40 cardiac units in Central Europe and North America, this book will be invaluable not only for both novice and experienced surgeons, but also for all physicians, nurses, and technicians caring for patients with heart disease of any type, at any age.
INTRODUCTION -- TECHNICAL PREREQUISITES -- Principles and Evolution of Extracorporeal Circulation -- Cardiovascular Tissue Engineering -- Adult Intensive Care Medicine in Cardiac Surgery -- Intensive Care Medicine in Pediatric -- CONGENITAL ANOMALIES OF HEART AND GREAT VESSELS -- Surgery for Congenital Heart Defects -- Anomalous Pulmonary Venous Drainage and Congenital Abnormalities of Atria, Atrioventricular Septum and AV-Valves -- Functional Univentricular Heart and Fontan Circulation -- Ventricular Septal Defects -- Anomalies of the Right Ventricular Outflow Tract -- Anomalies of the Left Ventricular Outflow Tract -- Aortic Atresia, Hypoplastic Left Heart Syndrome, and Hypoplastic Left Heart Complex -- Common Arterial Trunk -- D-Transposition of the Great Vessels and Congenitally Corrected Transposition -- Anomalies of the Coronary Arteries and Coronary Diseases in Children and Adolescents -- Anomalies of the Great Intrathoracic Vessels -- AQUIRED DISEASES OF HEART AND GREAT VESSELS -- Coronary Heart Disease -- Left Ventricular Reconstruction and Conventional Surgery for Cardiac Failure.
Keywords: Medicine; Critical care medicine; Cardiology; Surgery; Medicine & Public Health; Surgery; Cardiology; Intensive / Critical Care Medicine